Penggunaan Tanaman Herbal Bawang Putih (Allium Sativum L) Terhadap Aterosklerosis Penyebab Penyakit Jantung Koroner - Gracea S Manufandu; William William; William Wibowo (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Background: DKI Jakarta has the highest CAD disease rate at 1.9% based on the 2018 Riskesdas. Deaths from CAD are predicted to increase to 23.3 by 2030. Atherosclerosis is an inflammation that occurs due to the deposition of fat called atheroma. Currently, many studies are conducted to reduce cholesterol levels in the blood using natural ingredients such as garlic which is considered to have many advantages. The purpose of this study is to determine the important compounds in garlic that can reduce cholesterol levels, and become anti-atherosclerosis in blood vessels. Methods: Literature review based on articles and journals adjusted by PICO (Population, Intervention, Control, Outcome) and PRISMA Flow Diagram Generator method. Journals were searched in medical databases through Google Scholar, PubMed, and ProQuestd. Results: Based on the literature, garlic compounds that can reduce LDL levels and increase HDL have been studied, namely non-volatile γ-glutamyl-Salk(en)yl-L-cysteine or alliin . Conclusion: The presence of active compounds contained in garlic can significantly reduce the risk of atherosclerosis in coronary heart disease because it can reduce cholesterol levels in the blood and plaque in atherosclerosis.